Impact Of Enterprise Resource Planning (ERP) System Misfit On Information Quality : A Moderated Model Of Alignment Strategies - Tan, Shiang Yen (2012)
Businesses have moved away from “in-house developed” software systems to packaged systems developed by vendors for businesses in general since the past decade. One of the most prevalent packaged systems is Enterprise Resource Planning (ERP) system. ERP systems are now recognized as the enabler for businesses to achieve data integration, improve operational performance, and attain strategic advantage. However, more than half of the ERP implementations are reported as failed and did not achieve the expected benefits. Researchers have asserted that the failures are mainly attributed to ERP misfits, i.e. the misalignments between the ERP system functionalities and the organizational requirements.